Topography of the medullar cone in the giant anteater (Myrmecophaga tridactyla Linnaeus, 1758 - Ribeiro, Lucas de Assis; de Souza, Tharlianne Alici M.; Ribeiro, Priscilla Rosa Q.; dos Santos, Lázaro A.; Silva, Daniela Cristina de O.; Silva, Frederico O. Carneiro e; Barros, Roseâmely Angélica C.; Zanon, Renata Graciele (Brazilian Journal of Veterinary Medicine, 2015)
ABSTRACT. Ribeiro L.A., Souza T.A.M., Ribeiro P.R.Q., Santos L.A., Silva D.C.O., Carneiro e Silva F.O., Barros R.A.C. & Zanon R.G. [Topography of the medullar cone in the giant anteater (Myrmecophaga tridactyla Linnaeus, 1758.] Topografia do cone medular do Tamanduá-bandeira (Myrmecophaga tridactyla Linnaeus, 1758). Revista Brasileira de Medicina Veterinária, 37(4):353-358, 2015. Programa de Pós-Graduação em Ciências Veterinárias e Zootecnia, Faculdade de Medicina Veterinária, Universidade Federal de Uberlândia, Rua João Naves de Ávila, 2121, Uberlândia, MG 38408-100, Brasil. E-mail: lucasassis83@yahoo.com.br The giant anteater (Myrmecophaga tridactyla) is a representative of the Order Hairy, belonging to the family Myrmecophagidae. General approaches on the behavior, ecology and physical abilities of this animal are available in the literature. However, information regarding different aspects of the anatomy of the nervous system giant anteater are sparsely found. Therefore, the morphological knowledge of the relationship between the spinal cord and vertebral column is of great importance to the scientific, as in the various species of animals, whether domestic or not, the relations of the caudal spinal differ. This difference comes out to meet the interests of wild animal medicine, especially as support for the practice of epidural anesthesia. Thus, the objective was to describe the topography of the conus M. tridactyla, providing anatomical data as a basis for the practice of epidural anesthesia. For this study we used three specimens of giant anteater, prepared by the usual techniques in Macroscopic Anatomy, which had three sacral vertebrae and 4. Sendo que a base do cone medular foi registrada ao nível da terceira vértebra lombar (L3), com comprimento variando entre 3,5cm e 4,5cm e ápice localizando-se ao nível da segunda vértebra sacral (S2). These anatomical findings may point out as a safe place to perform epidural anesthesia, interarcual sacrococcygeal space.